2020
DOI: 10.1093/ibd/izaa030
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Costs of Inflammatory Bowel Diseases

Abstract: Background Mental health diagnoses (MHDs) were identified as significant drivers of inflammatory bowel disease (IBD)-related costs in an analysis titled “Cost of Care Initiative” supported by the Crohn’s & Colitis Foundation. In this subanalysis, we sought to characterize and compare IBD patients with and without MHDs based on insurance claims data in terms of demographic traits, medical utilization, and annualized costs of care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…[13][14][15][16][17] An analysis of administrative claims data demonstrated that both direct and indirect costs of care were significantly higher in patients with IBD and a co-existent common mental disorder, compared with IBD patients without. 18 However, although numerous studies have reported on symptoms of anxiety and depression in patients with IBD, these demonstrate greatly varying prevalence rates, up to 80% in some studies. 19,20 Some of this variation may reflect differences in the psychometric tools used to define the presence or absence of these disorders, 19,21,22 but uncertainties remain about the magnitude of this problem, 23 as well as the strength of the association between symptoms of common mental disorders and type of IBD, 13,24,25 the influence of IBD activity, [26][27][28] and the impact of sex.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] An analysis of administrative claims data demonstrated that both direct and indirect costs of care were significantly higher in patients with IBD and a co-existent common mental disorder, compared with IBD patients without. 18 However, although numerous studies have reported on symptoms of anxiety and depression in patients with IBD, these demonstrate greatly varying prevalence rates, up to 80% in some studies. 19,20 Some of this variation may reflect differences in the psychometric tools used to define the presence or absence of these disorders, 19,21,22 but uncertainties remain about the magnitude of this problem, 23 as well as the strength of the association between symptoms of common mental disorders and type of IBD, 13,24,25 the influence of IBD activity, [26][27][28] and the impact of sex.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression are the most common psychological disorders for patients with IBD. One recent study showed that patients with IBD and mental health disease generated significantly higher costs compared with patients without mental disorders (4). Psychological disorders in patients with IBD may lead to high risk of relapse and poor treatment compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the provision of psychiatric support at local community level make it hard to quantify with precision the impact of these disorders on IBD outpatient and emergency services in the UK. However, reports from Australia, the USA and the UK suggest that an integrated psychiatric service for patients with IBD, offered along the lines we advocate below, may reduce this impact and its related costs 6–8…”
Section: Introductionmentioning
confidence: 99%